On the threshold of mystery: Tomáš Halík on cultural witness in an age of uncertainty and change - McGrath, AE (MDPI, 2023)
Tomáš Halík (born 1 June 1948) has established himself as one of the most thoughtful commentators on public cultural witness in a time of change and uncertainty, especially in central Europe. As an academic at Charles University (founded 1348) and a Catholic priest in the “Academic Parish of Prague”, Halík played an important role during and following the collapse of Marxism in Czechoslovakia in the “Velvet Revolution” of November—December 1989, even being mentioned as a possible successor to Czech President Václav Havel, while at the same time offering reflections on religious engagement with a complex and changing secular culture. This article engages some leading themes of Halík’s approach to cultural witness, focusing especially on cultural quests for false certainties, the need for churches to create liminal spaces enabling seekers to grasp what lies at the heart of the Christian faith, the dangers of romanticizing a lost past of faith which encourages disengagement with the present, and the need to understand faith in terms of a constant movement of thought rather than a fixed system of ideas. The article considers how these ideas can find wider application in engaging the challenges of cultural witness, particularly in a European context, and what can be learned from them.